In commemoration of professor Olexiy Volodymyrovych Lyulko - DMA, SE (Medicni Perspektivi, 2013)
In commemoration of corresponding member of NAMS of Ukraine doctor of medical sciences, professor Olexiy Volodymyrovych Lyulko